The Relationship between Statin and Risk of Age-Related Macular Degeneration: A Systematic Review and Meta-Analysis - Ezatollah Memarzadeh; Saeid Heidari-Soureshjani (Journal of Ophthalmology)
Introduction and Aim. Age-related macular degeneration (AMD) is one of the leading causes of blindness and visual defect, particularly in elderly people across the world. This meta-analysis aimed at investigating the relationship between statin and the risk of AMD. Methods. Web of Science, PubMed, and Scopus databases were searched for articles that addressed the relationship between statin consumption and risk of AMD. The pooled odds ratio (OR) and 95% confidence interval (CI) were calculated using a random-effects model. Subgroup analyses and sensitivity analyses were also conducted. Cochran’s Q test and the I2 statistic were used to evaluate the heterogeneity. To assess potential publication bias, Begg’s test was used. Results. In total, 22 studies were reviewed in the meta-analysis that included 2063195 participants and 313702 (15.20%) AMD patients compared to individuals not receiving statins. The OR of AMD in statin-receiving participants was 0.93 (95% CI; 0.83–1.05, P=0.225). The OR of AMD in those that received statins was 0.92 (95% CI; 0.75–1.13, P=0.440) in case-control studies, 0.95 (95% CI; 0.82–1.09, P=0.458) in cohort studies, 0.951 (95% CI; 0.59–1.53, P=0.831) in cross-sectional studies, 0.94 (95% CI; 0.80–1.10, P=0.468) in North America, 0.81 (95% CI; 0.54–1.21, P=0.308) in Europe, 1.05 (95% CI; 0.94–1.18, P=0.362) in Asia, and 0.52 (95% CI; 0.26–1.04, P=0.125) in Australia. No publication bias was observed in this study (P=0.114). Conclusion. According to the results of this study, taking statins does not increase or decrease the risk of AMD development. Therefore, this drug group cannot be considered a protective or risk factor for the occurrence of AMD.